Next-Generation Sequencing of PTGS Genes Reveals an Increased Frequency of Non-synonymous Variants Among Patients With NSAID-Induced Liver Injury - Lucena, María Isabel; García-Martín, Elena; Daly, Ann K.; Blanca, Miguel; Andrade, Raúl J.; Agúndez, José A. G. (Frontiers in Genetics, 2019)
Purpose: The etiopathogenesis of drug-induced liver injury (DILI) is still far from being elucidated. This study aims to the study of genetic variations in DILI, related to the drug target, and specifically in the genes coding for the cyclooxygenase enzymes. Methods: By using Next-generation Sequencing we analyzed the genes coding for COX enzymes (PTGS1 and PTGS2) in 113 individuals, 13 of which were patients with DILI caused by COX-inhibitors. Results: The key findings of the study are the increased frequency, among DILI patients, of SNPs causing alterations in transcription factor binding sites and nonsynonymous PTGS gene variants, as compared to control subjects. Moreover, the association with nonsynonymous SNPs was exclusive of DILI patients with late-onset (50 days or more) Pc<0.001 as compared to DILI patients with early onset, or with control subjects. Conclusions: Our findings suggest an interaction of long-term exposure to COX inhibitors combined with functional variants of the COX enzymes in the risk of developing DILI. This is a novel observation that might have been overlooked by previous genetic studies on DILI because of the limited coverage of PTGS genes in exome chips.